Independent Test Verification: Consolidated Experience Report - Silva, Nuno; Lopes, Rui (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2012: Anais do XI Simpósio Brasileiro de Qualidade de SoftwareDO - 10.5753/sbqs.2012.15326, 2012)
Independent verification and validation (IV&V) has been a key process for decades, and is highlighted in several international certification standards. One of the activities described in the “ESA ISVV Guide” is independent test verification (stated as Integration/Unit Test Procedures and Test Data Verification). This activity is commonly overlooked since customers do not really see the added value of checking thoroughly the validation team work. This article presents the consolidated results of a large set of independent test verifications, including the main difficulties, results obtained and advantages/disadvantages for the industry of these activities. This study will support customers in opting-in or opting-out for this task in future IVV contracts since we provide factual results from some real case studies.